Two Stay Two Stray (TSTS) Assisted by Mind Mapping Media on Social Science Learning Outcomes - I Kadek Sandika Wirayasa; Gede Wira Bayu (Universitas Pendidikan Ganesha, 2023)
Elementary social studies learning is still dominated by the role of the teacher as a material provider. This causes student involvement in social studies learning to be less than optimal. This research aims to analyze the Two Stay Two Stray (TSTS) learning model assisted by mind mapping media on the social studies results of class V students. This research is a quasi-experimental type with a nonequivalent post-test-only control group design. The sample was determined using simple random sampling with a lottery technique. The research sample consisted of Class V. The data collection method was the test method. The data analysis technique in this research uses descriptive statistical analysis techniques and data analysis prerequisite tests. Hypothesis testing uses the polled variance t-test. The results of calculating the average social studies learning outcomes for experimental group students are very high, while students in the control group are in the medium category. Based on calculations using the t-test, there is a significant influence of the Two Stay Two Stray (TSTS) learning model assisted by mind mapping media on class V students' social studies learning outcomes. Therefore, the TSTS learning model assisted by mind mapping media is suitable for improving students' social studies learning outcomes. This research implies that teachers can think more creatively and gain new insights and experiences regarding implementing innovative learning in the classroom, which is useful for developing students' critical thinking patterns.